2022
DOI: 10.1038/s41590-022-01185-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial electron transport chain is necessary for NLRP3 inflammasome activation

Abstract: The NLRP3 inflammasome is linked to sterile and pathogen-dependent inflammation, and its dysregulation underlies many chronic diseases. Mitochondria have been implicated as regulators of the NLRP3 inflammasome through several mechanisms including generation of mitochondrial reactive oxygen species (ROS). Here, we report that mitochondrial electron transport chain (ETC) complex I, II, III and V inhibitors all prevent NLRP3 inflammasome activation. Ectopic expression of Saccharomyces cerevisiae NADH dehydrogenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 64 publications
6
103
0
1
Order By: Relevance
“…In the present study, it was moreover observed that the use of a glutaminolysis inhibitor reduced TNFα and IL-6 secretion following secondary stimulation in trained M(4/13) specifically, and not in untrained M(-) or M(IFNγ/LPS) (Figure 4A). This work suggests that OXPHOS can be important for pro-inflammatory responses, an observation that is supported by previous work demonstrating that for instance mitochondrial stress is a mechanism of macrophage tolerance (Timblin et al, 2021) and that the ETC is important for nod-like receptor family pyrin domain containing 3 (NLRP3) inflammasome activity (Billingham et al, 2022). It should be noted that in the latter study however, LPS induced TNFα secretion was not impeded by inhibition of ETC complexes I and II, demonstrating once more that the metabolic phenotype of the trained M(4/13), explored in the current study, is highly unexpected and warrants further study.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, it was moreover observed that the use of a glutaminolysis inhibitor reduced TNFα and IL-6 secretion following secondary stimulation in trained M(4/13) specifically, and not in untrained M(-) or M(IFNγ/LPS) (Figure 4A). This work suggests that OXPHOS can be important for pro-inflammatory responses, an observation that is supported by previous work demonstrating that for instance mitochondrial stress is a mechanism of macrophage tolerance (Timblin et al, 2021) and that the ETC is important for nod-like receptor family pyrin domain containing 3 (NLRP3) inflammasome activity (Billingham et al, 2022). It should be noted that in the latter study however, LPS induced TNFα secretion was not impeded by inhibition of ETC complexes I and II, demonstrating once more that the metabolic phenotype of the trained M(4/13), explored in the current study, is highly unexpected and warrants further study.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, although various ROS-dependent mechanisms have been invoked to sustain NLRP3 inflammasome signalling downstream of mitochondrial dysfunction 72 , ROS inhibitors seem to disrupt inflammasome priming (the synthesis of inflammasome components), but not activation (the acquisition of proteolytic activity) 73 . In line with this notion, recent data suggest that oxidative phosphorylation is involved in NLRP3 signalling driven by acute exposure to bacterial lipopolysaccharide (LPS) plus ATP 74 through a ROS-independent mechanism linked to preserved intracellular ATP availability via phosphocreatine 75 , although ROS seem to be necessary for long-term inflammasome activation upon prolonged exposure to β-amyloid. Moreover, conventional inflammasome activators such as LPS plus ATP seem to (elicit and) require mtDNA neosynthesis for optimal NLRP3 inflammasome signalling 76 .…”
Section: Mtdamp Signalling Pathwaysmentioning
confidence: 88%
“…During severe fever upon thrombocytopenia syndrome virus (SFTSV) infection, mtDNA is released into the cytosol through BAK/BAX signaling, which activates the NLRP3 inflammasome [ 128 ]. Moreover, the mitochondrial electron transport chain (ETC) is essential for NLRP3 inflammasome activation through the phosphocreatine-dependent generation of ATP [ 129 ].…”
Section: Cellular Mechanisms Driving Nlrp3 Inflammasome Activationmentioning
confidence: 99%